CURRENT CHEMICAL LEGISLATIVE EU REACH AT THE SECTION OF TECHNICAL EDUCATION - RUZINSKA, Eva; NEUPAUEROVA, Andrea (Trends in education, 2008)
The paper deals with the problem of registration, evaluation and authorization of chemicals due to valid european legislative orders and agreements guarding to heavy level of protection of human health and environmental.
Keywords: chemicals; REACH; environmental safety